Evaluation of efficacy of immunotherapy in children with asthma monosensitizied to Alternaria - Kilic, M.; Altintas, D.; Yilmaz, M.; Karakoc, G.; Burgut, R.; Kendirli, S. (Wiley-Blackwell, 2010)
[Abstract Not Available]
29th Congress of the European-Academy-of-Allergy-and-Clinical-Immunology (EAACI) -- JUN 05-09, 2010 -- London, ENGLAND